Hyperspectral sensing possibilities using continuum removal index in early detection of ganoderma in oil palm plantation - M.N. Maris, N.; M. Shafri, H.Z.; Idris, A.S.; Steven, M.; Boyd, D.; Mior, M.H.A. (2010)
This study focuses on the possibility of early detection of Basal Stem Rot (BSR) disease caused by Ganoderma spp. a wood decaying fungi in oil palm plantation. The datasets were based on reflectance spectra measured with a GER 1500 spectroradiometer in the range of 350 – 1050nm. Relationship of oil-palm leaves reflectance spectra with the infestation of BSR was investigated. Two datasets from the same plantation were analysed; the young palm (5 years old) and the mature palm (17 years old). The palms were classified to three groups: T1 – healthy palm, T2 – palm infected with Ganoderma without any foliar symptoms but with white mycelium or fruiting body at base stem; and T3 – palm infected with Ganoderma with foliar symptoms and white mycelium or fruiting body at base stem. The reflectance was analysed using the continuum removed at several absorption features; the blue region (400-550nm), red region (550 – 750nm) and the NIR region (915-970nm). The continuum removal vegetation indices; Band Depth, Normalised Band Depth, Difference to Reflectance, Band Depth Normalised to Area and Continuum Removed in three absorption features were analysed on the sensitivity of the infection. The results were compared to the results of several other hyperspectral indices namely Red-Edge, NDVI, SIPI, MCARI, TCARI and OSAVI. It can be concluded that most of the continuum removed indices in the three absorption features were possible to be use as a tool in early detection of BSR in oil palm plantation.